Estudos sobre a síntese de 4H-Cromenos promovida pelo pentacloreto de nióbio para utilização como corantes sensibilizadores em células solares - Oshiro, Paula Beatriz [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
4H-chromete derivatives constitute an important class of natural products, and the the interest in its chemical occurs because of the numerous biological and pharmaceutical effects, as well their use a intermediates in the synthesis of numerous natural products and medicinal reagents. These derivatives can be obtained thorugh the multicomponent reactions (MCR). The MCR's occur between three or more reagents in one reaction step only, in the same pot. These reactions have time and energy saving. The niobium pentachloride is strong Lewis acid, which has wide applicabiblity in organic reactions, including multicomponent reactions. Among, the various methods of synthesis of 4H-chromene derivatives, developed in this work, the synthesis by multicomponent reactions between benzaldehyde derivatives, 3,5-dimethoxyphenol and methyl acetoacetate, using niobium pentachloride as the Lewis acid, is described. The reactions were carried out at room temperature, under inert atmosphere (N2), using dichloromethane anhydrous (CH2Cl2) as solvent with a reaction time of 72 hours. The obtained products were isolated by column chromatography on silica gel and subject to analysis of structural characterization, photophysics and photochemistry for a study of their potential use as sensitizing dyes of Gratzel photoelectrochemical devices. Our results show that niobium pentachloride is a good promoter to multicomponent reaction studied, obtaining high yields (62-91%)

Os derivados de 4H-cromemos constituem uma importante classe de produtos naturais, e o interesse em sua química se dá por conta dos inúmeros efeitos biológicos e farmacêuticos, assim como sua utilização como intermediários nas sínteses de inúmeros produtos naturais e reagentes medicinais. Esses derivados podem ser obtidos através das reações multicomponentes (RMC). As RMC's ocorrem entre três ou mais reagentes em uma única etapa reacional, ao mesmo tempo frasco. São reações com economia de tempo e energia. O pentacloreto de nióbio é um ácido de Lewis forte, que apresenta grande aplicabilidade em reações orgânicas, incluindo as reações multicomponentes. Dentre os diversos métodos de síntese de derivados de 4H-cromenos, desenvolveu-se neste trabalho a síntese através da reação multicomponente entre derivados de benzaldeído, 3,5-dimetóxifenol e acetoacetato de metila, utilizando pentacloreto de nióbio como ácido de Lewis. As reações foram realizadas a temperatura ambiente, sob atmosfera inerte (n2) e utilizando diclorometano anidro (CH2Cl2) como solvente, com um tempo reacional de 72 horas. Os produtos obtidos foram isolados por coluna cromatográfica em sílica gel e submetidos a análises de caracterização estrutural, fotoquímica e fotofísica para um estudo de sua potencial aplicação como corantes sensibilizadores de dispositivos fotoeletroquímicos de Gratzel. A análise dos resultados obticos demonstram que o pentacloreto de nióbio é um bom promotor da reação multicomponente, obtendo-se bons rendimentos (62 a 91%)
Keywords: Niobium; Niobio; Pentaclorofenol; Celulas solares